PENGARUH PENYULUHAN TERHADAP PERUBAHAN PENGETAHUAN BAGI IBU-IBU PKK KELURAHAN PENGGARON LOR TENTANG PEMANFAATAN TANAMAN PISANG SEBAGAI MEDIA MENJAGA KESEHATAN GIGI DAN MULUT - Yayun Siti Rochmah; Minidian Fasitasari (Odonto : Dental Journal, 2014)
Background: Banana counted as nearly perfect food since it contains six nutrients : water , sugar , proteins , fats , vitamins , and minerals . Because of that , bananas are often used as a staple food for most people because of its nutritional value. However, sometimes people do not realize the benefits of bananas as a whole , from leaves , fruits , flowers and stems of the bananas . Penggaron Lor society , still minimal in using the banana plant . Usually the community will sell fruit and leaves to the market , so that the results obtained from the banana plant community less than optimal. Method : This study is an observational analytic study . The research was done in the Village of Penggaron Lor Semarang , and was conducted in March-June 2014. The instrument in this research was primary data obtained directly from respondents through interviews using questionnaires distributed before and after counseling . To determine whether there are differences in knowledge before and after counseling on the benefits of banana plants as a medium for maintaining oral hygiene, statistical test Wilcoxon Sign Ranks test was conducted, and processed with SPSS. Result: The results of SPSS calculation because the data is not normal ( p value < 0.05), then the data was processed using the non-parametric test for two sample pairs , ie Wilcoxon Sign Ranks test , and obtained p value of 0.008 . This means that there was a significant difference between the mean value of the pre-test and post-test. Conclusion : there are differences in knowledge before and after counseling , counseling means that a significant impact on respondents' knowledge of the benefits of banana plants for maintain oral health.